Characterization of Microbial Growth, Pathogen Presence, and Histamine Accumulation in Chilled Rainbow Trout and Mackerel Samples Collected from Romanian Markets - Vida Silviu; Alexandra Tabaran; Oana Lucia Crişan Reget; Mihaela Niculina Duma; Luciana Cătălina Panait; Sorin Daniel Dan (Pathogens, 2025)
This study aimed to evaluate microbial growth, pathogen presence, and histamine production in rainbow trout and mackerel stored on flaked ice over their shelf life. A total of 72 fish samples (rainbow trout and mackerel) were analyzed across four storage intervals (day 1, 3, 9, 12/11) on flaked ice. TVC increased from 2.59 to 5.04 log cfu/g in rainbow trout and from 3.18 to 4.88 log cfu/g in mackerel over the storage period. Significant increases were observed in Pseudomonas, Aeromonas, and Enterobacteriaceae populations, especially after the ninth day. Microbial identification revealed spoilage-associated bacteria, such as Pseudomonas fluorescens and Aeromonas salmonicida, as well as opportunistic pathogens, including Francisella tularensis, Yersinia spp., and Chromobacterium violaceum. Histamine levels rose with storage time but remained below toxic thresholds (<200 mg/kg), peaking at 1.56 mg/kg in trout and 1.87 mg/kg in mackerel. A strong positive correlation was found between TVC and histamine levels (Pearson’s r = 0.85 for trout, 0.82 for mackerel). Proper hygiene and storage are crucial, and consumption is recommended before day 9 of storage on flaked ice. Hygiene measures remain essential to minimize contamination risks and preserve product safety.